AN ANALYSIS OF TOUR GUIDES’ MULTILINGUALISM IN THE CITY OF BANDUNG, INDONESIA - Abdullah, Cep Ubad; Wulung, Shandra Rama Panji; Ruhimat, Mamat; Arrasyid, Riko (JURNAL PENDIDIKAN ILMU SOSIAL, 2020)
Language skills and diversity are important for the tourism industry in marketing their products and make it easier for foreign tourists to communicate while in tourism destinations. To measure and overcome this challenge is a reason to consider this research through a multilingualism program in the tourism industry in Greater Bandung. The purpose of this study is to analyze the policies and conditions of tourism multilingualism in Greater Bandung. This study also aims to discover the perceptions of the tourism industry related to multilingualism in Greater Bandung. The research approach uses qualitative and primary data collection methods obtained through observation and interviews. While secondary data obtained through policy documents and previous research. The method of analysis uses descriptive qualitative analysis and content analysis. The findings are expected to be able to know the existing conditions of local government policies related to multilingualism and tourism. Also, this research is expected to be able to identify perceptions of the tourism industry on the needs of multilingualism in Greater Bandung.